1-A-D-16. The characteristics of resting-state EEG connectivity in patients with Alzheimer's disease by the LORETA. Issue 6 (June 2015) - Nishida, Keiichiro; Pascual-Marqui, Roberto; Yoshimura, Masafumi; Kitaura, Yuichi; Mii, Hiroshi; Isotani, Toshiaki; Kinoshita, Toshihiko
Abstract : Alzheimer's disease (AD) is characterized by cognitive and memory dysfunctions, and is accompanied by default mode network (DMN) abnormalities. We investigated the neurophysiological basis of these dysfunctions by examining functional connectivity using standardized low resolution electromagnetic tomography (sLORETA). Resting, eyes closed EEGs were recorded from 19 patients with mild AD and 22 healthy control subjects. Electrophysiological connectivity maps between parahippocampal gyri and all other cortical regions were computed, as well as pairwise connectivity among DMN regions. Between-group comparisons in 7 frequency bands were carried out. Beta2 connectivity was marginally decreased between right parahippocampus and right superior frontal gyrus, right precentral gyrus, and right occipital lobe in AD patients. They also showed significantly decreased alpha2 and beta2 connectivity between posterior cingulate gyrus and right inferior parietal lobe within DMN. Previous fMRI studies have shown AD decreased connectivity between parahippocampus, where significant neurological degeneration appears, and other brain regions. The disconnection between the hubs of DMN in sLORETA connectivity suggest AD patients have an abnormal DMN, in agreement with previous fMRI resting state networks studies. sLORETA connectivity provides complimentary information on the neurophysiological dysfunction between parahippocampus and other cortical areas, and on the DMN aberrance in patients with AD.